2019
DOI: 10.3390/app9071449
|View full text |Cite
|
Sign up to set email alerts
|

Defect Detection using Power Spectrum of Torsional Waves in Guided-Wave Inspection of Pipelines

Abstract: Ultrasonic Guided-wave (UGW) testing of pipelines allows long-range assessment of pipe integrity from a single point of inspection. This technology uses a number of arrays of transducers separated by a distance from each other to generate a single axisymmetric (torsional) wave mode. The location of anomalies in the pipe is determined by inspectors using the received signal. Guided-waves are multimodal and dispersive. In practical tests, nonaxisymmetric waves are also received due to the nonideal testing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In each iteration, the signal is normalised, and its corresponding power spectrum is generated to detect the Torsional wave. However, due to significant changes in the excitation sequences, it is not recommended to use this algorithm with frequencies higher than 42 kHz [5].…”
Section: Pipesmentioning
confidence: 99%
See 1 more Smart Citation
“…In each iteration, the signal is normalised, and its corresponding power spectrum is generated to detect the Torsional wave. However, due to significant changes in the excitation sequences, it is not recommended to use this algorithm with frequencies higher than 42 kHz [5].…”
Section: Pipesmentioning
confidence: 99%
“…The multi-modal and dispersive nature of guided waves makes the signal processing particularly challenging, which has been the subject of several studies over the years [4][5][6]. The used techniques are not necessary only for the interpretation of the received ultrasonic signals but also for procedure automation, which improves the non-destructive testing and evaluation, along with their reliability and replicability.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the reflection coefficient of axisymmetric cracks increases monotonically with depth. Houman [16] proposed a method using the power spectrum difference between torsional waves and flexural waves to detect the torsional waves and determine the defect location. Kim and Park [17,18] used the basic torsional Sensors 2023, 23, 8734 2 of 12 mode to characterize the axial and inclined defects in the pipe and found that at a fixed depth of the defect, the reflection coefficient is a linear function of the ratio of the equivalent circumference range of the defect to the outer circumference of the pipe, and is almost independent of the axial range.…”
Section: Introductionmentioning
confidence: 99%
“…Performance degradation of pipelines will undoubtedly affect normal operation and cause serious accidents like explosions and leakages. In order to check the working state of pipelines, many researchers have proposed various effective methods, by which defects have been successfully detected [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%